(untitled) (Journal of the College of Basic Education, 2026)
Manuscripts are among the most prominent examples of remarkable cultural and cognitive development, reflecting society’s interest in science, arts, and literature. With the advent of the modern era and the growing interest in development, the importance of utilizing non-shared manuscripts has increased, given the direct connection between cultural identity and social and environmental development. This research aims to highlight the distinctive role of Islamic heritage in promoting a solid cultural identity, whereby cultural and civilized heritage is preserved with its distinctive characteristics, cultural features, arts, and ancient social values. The research also demonstrates that interest in manuscripts contributes to protecting cultural heritage from extinction, and compares cultural heritage with its cultural, social, and environmental dimensions.